Innovative Advisory Services in the Virtual World An Empowerment Perspective - Li, Manning; Liu, Jihong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
How to effectively design and deliver virtual advisory services can be a mystery to many public and private organisations. This study examines the interesting phenomenon of providing virtual advisors to assist users in accomplishing their tasks in the digital world. Based on a thorough analysis of abundant typical applications in various business and government sectors, this book discusses the current status and future trends of virtual advisory services in digital environments. This book also reveals exactly what users expect from such services, and what they hate! It provides thought-provoking guidelines for best practice in the design and provision of virtual advisors on e-portals.
Introduction -- Virtual advisors in the virtual world -- Virtual advisors in various application domains -- Preliminary data collections on user opinions about virtual advisors -- Discussion and Implications -- Conclusions.
Keywords: Economics; Social sciences; Economics/Management Science; Services; Business Strategy/Leadership.; Social Sciences, general